The Relationship Between Periodontal Status and Quality of Life in Type 2 Diabetes Patients in South Bariton - Pingkan Tulus Putri Martjun; Rr. Asyurati Asia; Yohana Yusra (Indonesian Journal of Global Health Research, 2025)
The global burden of type 2 diabetes mellitus continues to rise, and Indonesia is no exception. One of the major challenges faced by these patients is poor oral health, particularly periodontal disease, which can diminish overall well-being. This study aimed to examine how periodontal health relates to the quality of life of individuals with T2DM in South Barito. A cross-sectional design was employed, involving diabetic patients who sought care at local health facilities. Periodontal condition was measured using the Community Periodontal Index of Treatment Needs, whereas oral health-related quality of life was assessed through the Oral Health Impact Profile-14. Data analysis was conducted with a significance threshold of p<0.05. The findings revealed that patients with more severe periodontal issues (higher CPITN scores) experienced significantly poorer quality of life, particularly in domains such as daily functioning, pain, psychological well-being, and social interaction. A significant inverse correlation was identified between periodontal status and quality of life (p<0.05). These results highlight the importance of periodontal care as an integral component of diabetes management to help improve patients’ quality of life.